Bi-doped graphitic carbon nitride nanotubes boost the photocatalytic degradation of Rhodamine B. (17th January 2022) - Gao, Qingqing; Lei, Qian; Miao, Ruoyan; Gao, Manyi; Liu, Hu; Yang, Qin; Liu, Yequn; Song, Fang; Yu, Yongsheng; Yang, Weiwei
Abstract : Polymeric carbon nitride (PCN) is an emerging metal-free photocatalyst with high stability but is plagued by low photocatalytic efficiency due to the rapid charge carrier recombination behavior. Abstract : Polymeric carbon nitride (PCN) is an emerging metal-free photocatalyst with high stability but is plagued by low photocatalytic efficiency due to the rapid charge carrier recombination behavior. Herein, Bi-doped graphitic carbon nitride nanotubes (BCN nanotubes) with a porous structure have been facilely prepared by one-step thermal polymerization of mixtures of melamine, urea and bismuth nitrate pentahydrate under an Ar atmosphere. With unique structural advantages for charge carrier transfer, light harvesting, and large surface area, the as-prepared BCN nanotubes exhibit excellent photocatalytic activity for the degradation of Rhodamine (Rh) B with a 26.8-fold higher reaction rate than that of PCN under visible light irradiation. This work provides informative principles about the synthesis of PCN with controlled morphology and element doping simultaneously for the photocatalytic degradation of chemical pollutants.